Caused by Kozyavkin© method changes in hand function parameters in children with spastic form of cerebral palsy and their EEGs, HRVs and GDVs accompaniments - O V Kozyavkina; N V Kozyavkina; Т B Voloshyn; М S Hordiyevych; V I Lysovych; V Y Babelyuk; H I Dubkova; T A Korolyshyn; I R Mysula; D V Popovych; W Zukow; I L Popovych (Kazimierz Wielki University, 2018)
Background. Earlier we reported that in children with spastic forms of cerebral palsy (SFCP) after two-week course of rehabilitation by Kozyavkin© method the hand function tests changed ambiguously and such a variety of changes is due to differently directed changes in the background activity of the nerve centers. Aime: to identify the peculiarities of changes in the parameters of EEG, HRV and GDV in children with favorable and unfavorable changes in the parameters of the functions of the hands. Material and research methods. The object of observations were 14 children (6 girls and 8 boys) aged 8÷15 years with SFCP. State motor development at GMFCS was on II÷IV level. Functional status of the hand with MACS was at II÷III level. The estimation of hand function carried out by Dynamometry (D), Box and Block Test (BB) and Nine Hole Peg Test (NHP). We registered also components of muscular tone by device "NeuroFlexor" (Aggero MedTech AB, Sweden), HRV and EEG parameters simultaneosly by hardware-software complex "Cardiolab+VSR" and "NeuroCom Standard" respectively (KhAI Medica, Kharkiv, Ukraine) as well as GDV parameters by "GDV Chamber" ("Biotechprogress", St-Pb, RF). Results. The method of cluster analysis retrospectively highlighted two distinct groups-clusters. In 9 children, rehabilitation led to favorable changes in the parameters of the function of the hands, while in 3 children they turned out to be unfavorable. The method of discriminant analysis revealed that unfavorable changes are accompanied by a decrease in the asymmetry of the θ- and δ-rhythms, the spectral power density (SPD) of β-rhythm in loci F8 and Fp1, instead, it increases in loci O1 and T3, leading to left-sided lateralization of the β-rhythm. At the same time, the SPD of the α-rhythm in locus O1 and the θ-rhythm in locus F4 rises as well as its Deviation. These changes in the EEG are accompanied by a reduction in vagalis and an increase in sympathetic tones. Among the GDVs parameters, an increase in the area of the GD Image in the frontal projection, coupled with a decrease in its Entropy in the frontal and left projections, was found. Instead, favorable changes in the parameters of the hand function are accompanied by opposite changes in the listed EEGs, HRVs and GDVs parameters or their absence. Conclusion. Among 14 observed children with spastic forms of cerebral palsy caused by Kozyavkin© method changes in functional tests of hand are favorable in 11. Adverse changes in 3 children are accompanied by characteristic changes in a number of EEGs, HRVs and GDVs parameters, which in the long run will be corrected by electrostimulation of the corresponding nervous structures.